SHARED READING AND EMERGENT LITERACY IN EARLY CHILDHOOD EDUCATION: A LITERATURE REVIEW - Miranda, Fabiane; Martins, Rosemari Lorenz (Seven Editora, 2026)
Emergent literacy encompasses a set of skills that develop from early childhood and precede formal literacy, involving aspects of oral language, phonological awareness, vocabulary, and meaningful contact with written culture. Shared reading has been identified in the literature as a relevant pedagogical practice for the development of these skills, promoting interaction between adults and children and favoring the construction of meaning around the literary text. In this context, this work aims to analyze, through a literature review, the contributions of shared reading to the development of emergent literacy in Early Childhood Education. This is a narrative review, based on scientific productions selected from national and international databases, considering criteria of thematic and methodological relevance. The studies analyzed show that shared reading contributes to the expansion of vocabulary, the development of oral language, the organization of narrative, and the strengthening of the child’s connection with social reading practices, in addition to favoring children’s protagonism in the knowledge construction process. It is concluded that shared reading, when carried out intentionally and with mediation, constitutes a powerful pedagogical strategy for promoting emergent literacy, with significant implications for teaching practice and for the formation of readers from childhood. DOI: https://doi.org/10.56238/sevened2026.001-004